2012
DOI: 10.4038/seajme.v6i2.165
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspective of the MBBS Physiology curriculum

Abstract: Introduction: Rapid technological advances and information overload in the medical field calls for a redesigning of the medical curriculum especially in basic sciences. To incorpate change in the curriculum would require experts' opinion in the area. At the same time, students' opinion also forms an important basis for any modification. The present study is small one but it is an important step for this field. We have addressed this issue by evaluating students' perspective of the physiology curriculum with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, there are numerous studies that emphasize students' preferences for interactive teaching instead of lectures, which is consistent with our study findings. Chawla et al observed that 76% of students preferred tutorials and interactive small-group teachings, and almost all insisted that lectures should be more interactive and informative [9]. Another study by Costa et al also showed student preference for interactive teaching as the mode of learning [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are numerous studies that emphasize students' preferences for interactive teaching instead of lectures, which is consistent with our study findings. Chawla et al observed that 76% of students preferred tutorials and interactive small-group teachings, and almost all insisted that lectures should be more interactive and informative [9]. Another study by Costa et al also showed student preference for interactive teaching as the mode of learning [10].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the earlier study done by Dr. Omna Chawla. 6 It is shown that knowledge of basic science with clinical relevance is understood better and applied by students without any difficulty. The fact that basic science knowledge is a requisite to be a competent clinician is borne in the mind s of the students.…”
Section: Discussionmentioning
confidence: 99%